Italian fascism and antifascism : a critical anthology - Pugliese, Stanislao G., 1965- (Manchester ; New York : Manchester University Press : Distributed exclusively in the USA by Palgrave, 2001)
When the historical significance of fascism and anti-fascism is still being debated in Italy and across Europe, this comprehensive anthology offers an unusually wide-ranging collection of Italian-language documents. It effectively in describes and depicts a wide range of voices--political, literary, and popular--that illuminate Italy's social, political, and cultural history. The contributors unveil previously unavailable documents, including letters from women to Mussolini, and antifascist graffiti from a Nazi prison in Rome.
Contributors include: Umberto Eco, Benito Mussolini, Antonio Gramsci, Carlo Levi, Primo Levi, Robert Katz, Ada Gobetti, Antonio Fossati, Carlo Rosselli, Fausto Coen, Guiseppe Bottai, Filippo Tommaso Marinetti, Alcide Cervi, Benedetto Croce, Carla Capponi, Margherita Sarfatti, Giacomo Matteotti, Nicolo Tranfaglia, Cesare Pavese, Curzio Malaparte, Don Luigi Sturzo, Enrico Corradini, Gabriele D'Annunzio, Raffaele Cadorna, Geatano Salvemini, Teresa Noce, Arrigo Paladini, Luigi Capriolo, Roberto Farinacci, Giovanni Gentile, Giovanni Papini, Ignazio Silone, Italo Balbo, Palmiro Togliatti, Piero Gobetti, Renata Vigano, Renzo De Felice.
Texts in Italian with notes in English.
The Roger Griffin ComFas Collection
Keywords: Fascism -- Italy -- History; Anti-fascist movements -- Italy -- History; Italy -- Politics and government -- 1914-1945.